A Holistic Approach to Bone Tumors in Dogs and Cats: Radiographic and Histologic Correlation. Issue 5 (September 2021) - Dittmer, Keren E.; Pemberton, Sarah
The skeletal system is a common site for neoplasia in dogs and cats, and primary bone tumors may develop from any of the mesenchymal tissues present in bone. Imaging and histopathology are routinely used in the diagnosis of bone tumors, and the 2 techniques are highly complementary. While imaging may be highly suggestive of a specific diagnosis and treatment may be instituted based on this, definitive diagnosis requires histopathology of either incisional or excisional biopsies or an amputation specimen. However, there are a number of diagnostic dilemmas when the pathologist interprets bone biopsy samples, such as distinguishing reactive bone and tumor bone, fracture callus and tumor bone, different benign fibro-osseous lesions, and different types of bone sarcoma. This review outlines the characteristic radiographic and histologic changes associated with these diagnostic problems to aid in resolving them. When a holistic approach is taken to evaluation of the signalment, history, and clinical, radiologic, and microscopic features, a diagnosis may be possible. The pathologist is greatly assisted in the interpretation of bone samples by having access to imaging and should routinely request either the images or the imaging reports if they are not received from submitting veterinarians.